PS34 Recording and Management of Obesity in Primary Care, 1997-2006. (17th September 2012) - Booth, HP; Gulliford, M
Abstract : Background: Primary care services play a potentially important role in the diagnosis and management of obesity but little evidence exists on current routine practice. The aim of this study was to describe the recording of body mass index and interventions used in the management of body weight in UK primary care in different categories of body weight. Methods: A retrospective cohort study was implemented using the UK General Practice Research Database (GPRD). Participants were aged between 18 and 100 and had a diagnosis of obesity and/or a record indicating a weight management intervention between 1997 and 2006. Diagnoses of obesity were identified by a medical code for obesity or a body mass index (BMI) record of ≥30kg/m 2 .Interventions were identified by medical and therapy codes and included advice on diet, body weight control or exercise, referral to specialist care for obesity or prescription of anti-obesity drugs. Results: Patients (n=69, 102) with a diagnosis of obesity or who received a weight management intervention were identified at 128 UK general practices. Average BMI rose slightly over the study period from 35.0kg/m 2 in 1997 to 35.8kg/m 2 in 2006, with a higher proportion of patients gaining rather than losing or maintaining their weight each year. Monitoring of BMI was infrequent with just 48% of patients previously identified as obese having a BMI recorded in 2006. The proportion of patients with one or more interventions for weight control recorded increased from 29% in 1997 to 37% in 2006. The most frequent intervention throughout the study period was the provision of dietary advice, recorded in 13, 097 (40.7%) patients in 2006 compared to 3, 401 (32.3%) in 1997. Prescription of anti-obesity drugs increased by almost 60-fold over the study period. The proportion of morbidly obese patients (BMI ≥40kg/m 2 ) receiving a weight control intervention in 1997 was 38%, rising to 63% in 2006. In obesity category I (BMI 30–34.9kg/m 2 ) the proportion receiving treatment was 43% in 1997 and 53% in 2006 and in category II (BMI 35–39.9kg/m 2 ) 41% and 56% respectively. Conclusion: Monitoring of obesity in diagnosed patients was inconsistent in this population with less than half having a BMI recorded in each year of the study. The frequency of interventions for weight management increased substantially in primary care between 1997 and 2006.